Analysis of Ibnu Taymiyyah's Fatwa on Inheritance Among Different Religions and its Relevance in the Modern Era - Muhibban; Hasan, Nur (PT Elaborium Elevasi Indonesia, 2025)
This study discusses the analysis of Ibn Taymiyyah’s fatwa on interfaith inheritance, with the background of differing opinions among Islamic scholars regarding whether inheritance between adherents of different religions is permissible. It also explores the relevance of this issue in today’s pluralistic and multicultural society. The aim of this research is to gain an in-depth understanding of Ibn Taymiyyah’s perspective, to comprehend the arguments he employed, and to assess the extent to which his fatwa can be applied in the modern era. This study uses a qualitative method with a library research approach by analyzing the works of Ibn Taymiyyah and the views of related scholars. The findings show that Ibn Taymiyyah’s opinion—that a Muslim may inherit from a non-Muslim—is based on a specific interpretation of the term kāfir in the hadith, supported by examples from the practices of the Prophet’s companions and considerations of public interest (maṣlaḥah). This reflects the relevance and argumentative strength of his view both academically and socially. The conclusion of this study is that Ibn Taymiyyah’s fatwa remains relevant and worthy of consideration in addressing complex and diverse issues of inheritance law in the modern world